1988
DOI: 10.1111/j.1464-410x.1988.tb06381.x
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic Findings following Radiotherapy for Cervical Carcinoma

Abstract: Forty patients were assessed urodynamically 5 to 11 years after radiotherapy for cervical carcinoma and compared with 27 patients prior to treatment. The mean volume of first bladder sensation after radiotherapy was significantly lower than the mean volume before treatment, as was the mean maximum cystometric capacity. The mean filling detrusor pressure was higher after radiotherapy than before treatment. Unstable detrusor contractions were found only in the 12 symptomatic patients. There was a significant red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…These complications include irritative bladder symptoms, stress incontinence, abnormal voiding function, and radiation cystitis [7, 8]. In cervical cancer, severe urinary complications requiring surgery and urinary diversion can present much later after completion of radiation treatment, with one study reporting an average onset of severe urinary symptoms 15 years after radiation treatment [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These complications include irritative bladder symptoms, stress incontinence, abnormal voiding function, and radiation cystitis [7, 8]. In cervical cancer, severe urinary complications requiring surgery and urinary diversion can present much later after completion of radiation treatment, with one study reporting an average onset of severe urinary symptoms 15 years after radiation treatment [8].…”
Section: Discussionmentioning
confidence: 99%
“…Perkin et al examined urodynamic findings in 40 women after radiation therapy as the primary treatment for cervical cancer (without hysterectomy) compared to 26 women newly diagnosed with cervical cancer prior to treatment [7]. These authors found a difference in maximum cystometric capacity (284.8 vs. 346.4 ml, p <0.02), detrusor pressure (13.9 vs. 4.2 cmH2O, p <0.01), and maximum urethral closure pressure (56.7 vs. 65.8 cmH2O, p <0.05) between the two groups of women.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, urinary flow would be expected to be markedly reduced. Urinary incontinence is especially 368 K. Hamada et al common in women who have undergone radical surgery [10]. Urinary incontinence, as measured by the pad test, was more severe in the radical hysterectomy-only group than in the radiation therapy-only group, but urethral pressure was not significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 88%
“…It is well known that the urethral pressure gradually decreases with aging [1,2,5]: patients in the radiation therapy-only group were older than the other groups. In addition, radiation-induced urethral change may also decrease the urethral pressure [10]. It is reported that radiation produces severe fibrosis of the bladder wall with smooth muscle degeneration [11], which may be attributed to the direct effects of radiation on the muscle cells and to ischemia following vascular damage of perivascular smooth muscle cells [12].…”
Section: Discussionmentioning
confidence: 99%
“…Patients experiencing urgency, frequency or incontinence were excluded. In view of the 33% incidence of DO known to occur after previous pelvic irradiation [Parkin et al, 1988], such patients were also excluded.…”
Section: Diagnosis and Patient Selectionmentioning
confidence: 99%